Multicomponent crystals of nitrofurazone – when more is less. Issue 7 (11th January 2019) - Sharara, Kudzaishe N.; Nyamayaro, Kudzanai; Wicht, Merrill M.; Venter, Gerhard A.; Báthori, Nikoletta B.
Abstract : Multicomponent crystal formation of nitrofurazone was challenging when the experimental work was based on popular crystal engineering principles. Abstract : Multicomponent crystal formation of nitrofurazone, a conformationally flexible drug that is capable of forming various supramolecular synthons, was challenging when coformers were selected based on popular crystal engineering principles.